Challenge in the discovery of new drugs: Antimicrobial peptides against who‐list of critical and high‐priority bacteria - Roque‐borda, Cesar Augusto [UNESP]; da Silva, Patricia Bento; Rodrigues, Mosar Corrêa; Azevedo, Ricardo Bentes; Di Filippo, Leonardo [UNESP]; Duarte, Jonatas L. [UNESP]; Chorilli, Marlus [UNESP]; Vicente, Eduardo Festozo [UNESP]; Pavan, Fernando Rogério [UNESP] (MDPI, 2021)
Bacterial resistance has intensified in recent years due to the uncontrolled use of conventional drugs, and new bacterial strains with multiple resistance have been reported. This problem may be solved by using antimicrobial peptides (AMPs), which fulfill their bactericidal activity without developing much bacterial resistance. The rapid interaction between AMPs and the bacterial cell membrane means that the bacteria cannot easily develop resistance mechanisms. In addition, various drugs for clinical use have lost their effect as a conventional treatment; however, the synergistic effect of AMPs with these drugs would help to reactivate and enhance antimicrobial activity. Their efficiency against multi‐resistant and extensively resistant bacteria has positioned them as promising molecules to replace or improve conventional drugs. In this review, we examined the importance of antimicrobial peptides and their successful activity against critical and high‐priority bacteria published in the WHO list.
Keywords: AMPs; Antibacterial activity; Critical‐priority bacteria; High‐priority bacteria; MDR; XDR